Newly Identified Roles of PML in Stem Cell Biology - Ito, Keisuke; Ito, Kyoko (Frontiers in Oncology, 2013)
It has long been believed that the tumor suppressor promyelocytic leukemia (PML), the core component of the nuclear substructures known as the PML-nuclear bodies, plays a key part in acute promyelocytic leukemia (APL), as it is first cloned at the breakpoint of the t(15;17) translocation typical of that disease. Research over the past decade, however, has radically changed our view of how this tumor suppressor is regulated, how it can be therapeutically targeted, and how it functions in a number of tissue systems. One noteworthy recent study, for instance, revealed that PML regulates the activation of fatty acid metabolism, and that this metabolic reprogramming plays an essential role in cancer biology and stem cell biology through the control it exerts over stem cell fate decisions. These findings sparked exciting new investigations of PML as a critical ‘rheostat’ responsible for fine-tuning tissue homeostasis, and thus created at the intersection of cancer and stem cell biology a new field of study with important therapeutic implications.